The use of mixed methods to identify typology of poverty in East Java, Indonesia - Doddy Sumbodo Singgih; Sudarso Sudarso; Siti Mas'udah (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2020)
This article describes the results of concurrent mixed method testing to identify the typology of poverty in one particular area in East Java, Indonesia known as the